2017
DOI: 10.1007/s10340-017-0835-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of adult diet on parasitoid reproductive performance

Abstract: Diet is one of the most common influences on parasitoid reproductive traits. The life span, mating ability, fecundity, fertility and sex ratio of parasitoids can be affected by the quality of the adult diet. In the field, parasitoids can rely on different hosts and non-host nutrient sources, such as floral and extrafloral nectar, hemipteran honeydew and pollen, and various artificial diets have been used in mass rearing. In addition, some parasitoid species obtain nutrients by feeding on their host while adult (hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 156 publications
5
84
0
Order By: Relevance
“…Other traits that may be important, such as the amount and quality of nectar, were data deficient so not included. The quality of nectar may also adversely affect parasitoids, such as the presence of melezitose which reduces some parasitic wasps' longevity and oviposition rate . Parasitoids may also avoid some nectars because of secondary compounds and antimicrobial proteins .…”
Section: Discussionmentioning
confidence: 99%
“…Other traits that may be important, such as the amount and quality of nectar, were data deficient so not included. The quality of nectar may also adversely affect parasitoids, such as the presence of melezitose which reduces some parasitic wasps' longevity and oviposition rate . Parasitoids may also avoid some nectars because of secondary compounds and antimicrobial proteins .…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that honeydew volatiles are important kairomones for parasitoids and predators, and these volatiles can improve the efficacy of natural enemies (Almohamad et al, 2009;Leroy et al, 2011). Many studies have indicated that the composition of aphid honeydew obviously influences the performance of aphid enemies (Hogervorst et al, 2007;Hagenbucher et al, 2014;Tena et al, 2016;Zhou et al, 2016;Benelli et al, 2017). However, relatively few studies have evaluated the quantitative effects.…”
Section: Discussionmentioning
confidence: 99%
“…This important finding has important implications for their effects on biological control in adjacent crops. Literature shows that increased reproductive lifespan enhances fecundity as well as host parasitism in general (Heimpel & Jervis, 2005;Benelli et al, 2017) as well as specifically for D. rapae (Tylianakis et al, 2004;Jamont et al, 2013), D. semiclausum (Yang et al, 1993;Winkler et al, 2006), and C. glomerata (Hasan & Ansari, 2010). The extent of longevity benefit to parasitoids varied depending on the flower species and interplay between flower species and parasitoid species.…”
Section: Discussionmentioning
confidence: 99%